The Administrative Presidency: Presidential Directives and Executive Policymaking - Belco, Michelle H. author. aut Link
XIII, 431 p. 18 illus., 17 illus. in color.
Keywords: Presidential directives are a valuable tool for executive policymaking. Acting administratively, they are an exercise of executive power where presidents seem to be acting alone but, on reflection, may not be acting in isolation. Their directives may be an appeal to Congress for support or issued in lieu of legislation. At times, the decisions of the Supreme Court may help or hinder executive action. Meanwhile, within their own separate institution, presidents must rely on the federal bureaucracy to carry out their orders. This book systematically examines the use of presidential directives – executive orders, memoranda, and proclamations - to shape race policy. It uses a mixed-methods approach to analysing presidential directives from Presidents Nixon to Biden within this distinct policy area. By exploring the use of presidential directives, this book reveals the contributions of each president as well as the similarities and differences between them. The expansive time frame of this book provides an opportunity to investigate the origins of presidential policy on race to the Supreme Court’s decision to end affirmative action in higher education which marked a significant shift in race policy moving forward. Michelle Belco’s latest book provides the most comprehensive study about how presidents use unilateral directives to shape race policy during the modern presidency. This impressive book is a welcome addition for scholars of the American presidency, minority politics, and public policy. -Adam L. Warber, Clemson University. Michelle H. Belco, J.D., Ph.D., is a Senior Lecturer in Political Science at the University of Houston Honors College.